A Study on the Effect of Patient Characteristics, Geographical Utilization, and Patient Outcomes for Total Pancreatectomy Alone and Total Pancreatectomy With Islet Autotransplantation in Patients With Pancreatitis in the United States. Issue 9 (October 2019) - Lara, Luis F.; Bellin, Melena D.; Ugbarugba, Emmanuel; Nathan, Jaimie D.; Witkowski, Piotr; Wijkstrom, Martin; Steel, Jennifer L.; Smith, Kerrington D.; Singh, Vikesh K.; Schwarzenberg, Sarah J.; Pruett, Timothy L.; Naziruddin, Bashoo; et al.
Abstract : Objectives: A selective therapy for pancreatitis is total pancreatectomy and islet autotransplantation. Outcomes and geographical variability of patients who had total pancreatectomy (TP) alone or total pancreatectomy with islet autotransplantation (TPIAT) were assessed. Methods: Data were obtained from the Healthcare Cost and Utilization Project National Inpatient Sample database. Weighed univariate and multivariate analyses were performed to determine the effect of measured variables on outcomes. Results: Between 2002 and 2013, there were 1006 TP and 825 TPIAT in patients with a diagnosis of chronic pancreatitis, and 1705 TP and 830 TPIAT for any diagnosis of pancreatitis. The majority of the TP and TPIAT were performed in larger urban hospitals. Costs were similar for TP and TPIAT for chronic pancreatitis but were lower for TPIAT compared with TP for any type of pancreatitis. The trend for TP and TPIAT was significant in all geographical areas during the study period. Conclusions: There is an increasing trend of both TP and TPIAT. Certain groups are more likely to be offered TPIAT compared with TP alone. More data are needed to understand disparities and barriers to TPIAT, and long-term outcomes of TPIAT such as pain control and glucose intolerance need further study. Abstract : Supplemental digital content is available in the text.